WF SS-OCTA for detecting diabetic retinopathy and evaluating the effect of photocoagulation on posterior vitreous detachment - Gong, Yi; Hu, Liying; Wang, Linni; Shao, Yan; Li, Xiaorong (Frontiers in Endocrinology, 2022)
Purpose: This study aimed to assess the clinical usefulness of widefield swept source optical coherence tomography angiography (WF SS-OCTA) for detecting microvasculature lesions in diabetic retinopathy (DR) by comparing it with ultra-widefield fluorescein angiography (UWFFA) and to investigate the effect of panretinal photocoagulation (PRP) on posterior vitreous detachment (PVD) status. Methods: Patients with severe non-proliferative DR (NPDR) or proliferative DR (PDR) who were initially treated with PRP were enrolled. They underwent WF SS-OCTA with a 12×12-mm scan pattern of five visual fixations at baseline and at least a 3-month follow-up after PRP treatment. Patients with no contraindications underwent imaging with UWFFA within a week. Images were evaluated using two methods for the areas of the visible field of view (FOV), non-perfusion area (NPA), presence of neovascularization of the disc (NVD), neovascularization elsewhere (NVE), and PVD status. Results: In total, 44 eyes of 28 patients with DR that were initially treated with PRP were analyzed. The FOV of the UWFFA was significantly wider than that of the WF SS-OCTA. The quantitative measurement of the NPAs was consistent between the two methods. NPAs more than 5DA outside the panoramic OCTA imaging area were detected in 1 eye with NPDR (8.3%) and in 10 eyes with PDR (47.8%). WF SS-OCTA had high detection rates for NVDs and NVEs, with a low rate of false positives. After PRP treatment, no eyes indicated progression in the PVD stages around the macula, optical disc, or NVEs at the short follow-up. Conclusion: WF SS-OCTA is clinically useful for evaluating NPAs and neovascularization in DR. PRP treatment does not induce PVD development in the short term.